2018
DOI: 10.1186/s12879-018-3278-3
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate change during chronic hepatitis C treatment with Sofosbuvir/Ledipasvir in HCV/HIV Coinfected patients treated with Tenofovir and a boosted protease inhibitor: an observational prospective study

Abstract: IntroductionConcomitant use of ledipasvir and boosted protease inhibitors (PIs) may increase the risk of tenofovir (TDF) nephrotoxicity, since both these drugs increase TDF levels. Our aim was to evaluate glomerular filtration rate (eGFR) evolution during HCV treatment with sofosbuvir/ledipasvir (SOF/LDV) in HCV/HIV coinfected patients, according to their antiretroviral treatment (ARV).MethodsObservational prospective study of HCV/HIV coinfected patients treated with SOF/LDV. eGFR evolution was evaluated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…LDV, an inhibitor of P-glycoprotein and BCRP efflux transporters, may increase tenofovir concentration when given with TDF, which may increase the risk of TDF-related nephrotoxicity. In contrast, two studies showed that TDF was not associated with increased risk of nephrotoxicity in patients treated with LDV/SOF [38,39]. In our study, 6.1% (n = 7) patients had a switch of their cART regimens to avoid TDF, while 18.4% (n = 21) continued TDF.…”
Section: Discussioncontrasting
confidence: 77%
“…LDV, an inhibitor of P-glycoprotein and BCRP efflux transporters, may increase tenofovir concentration when given with TDF, which may increase the risk of TDF-related nephrotoxicity. In contrast, two studies showed that TDF was not associated with increased risk of nephrotoxicity in patients treated with LDV/SOF [38,39]. In our study, 6.1% (n = 7) patients had a switch of their cART regimens to avoid TDF, while 18.4% (n = 21) continued TDF.…”
Section: Discussioncontrasting
confidence: 77%
“…Butt and colleagues examined a large cohort of HCV‐infected Veterans and demographically matched HCV uninfected controls (ERCHIVES) to evaluate the risk of worsening kidney function, defined as a decline in eGFR >30 ml/min/1.73 m 2 from baseline, and found a statistically significantly lower risk associated with SOF‐containing vs non‐SOF‐containing regimens 32 . Finally, recent studies that have confirmed the kidney safety of coadministration of SOF with tenofovir‐based treatments in HIV/HCV co‐infected patients further corroborate this study’s findings 33,34 …”
Section: Discussionsupporting
confidence: 58%
“…Soeiro et al prospectively assessed the eGFR changes during SOF/LDV treatment in HIV/HCV‐coinfected patients on TDF‐based and TDF‐free ART. Although the eGFR decline between baseline and end of treatment of SOF/LDV was numerically higher in patients on TDF‐based ART (5.40 ml/min/1.73 m 2 for non‐boosted TDF regimen; 4.31 ml/min/1.73 m 2 for non‐boosted TDF regimen) than those on TDF‐free ART (2.02 ml/min/1.73 m 2 for non‐TDF regimen), the differences did not reach statistical significance by paired t ‐test 21 . By applying the GEE model for repeated eGFR measurements at 10 different time points with only 0.7% missing data, our study indicated that patients on TFV‐based ART had a slight but significant eGFR decline (adjusted slope difference: −0.82 ml/min/1.73 m 2 /month) compared to those on TFV‐free ART during SOF‐based DAAs.…”
Section: Discussionmentioning
confidence: 87%
“…Two case reports indicated that the use of SOF may increase the risk of acute kidney injury (AKI) in patients on TFV‐based ART 18,19 . However, other studies showed that the risks of AKI and estimated glomerular filtration rate (eGFR) decline during SOF‐based DAA therapy were comparable in HIV/HCV‐coinfected patients irrespectively of ART regimen 20–22 . Because most studies were retrospective and lacked protocol‐defined time point assessment for eGFR, or recruited limited numbers of patients, the link between SOF and TFV to nephrotoxicity in HIV/HCV‐coinfected patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%